السياسات البيئية في الجزائر وتأثيرها على المحليات - هباش الصالح (جامعة المسيلة, 2022)
يهدف البحث إلى معرفة مدى تأثير السياسات البيئية على المحليات، نحو مدن أكثر استدامة، ویتزاید الاھتمام بقضیة حمایة البیئة من التلوث واستنفاذ الموارد بشكل مستمر، وقد تجسد ھذا الاھتمام البیئي في صور عدیدة على المستویات المحلیة والعالمية، كما نجد أن قضايا البيئة تحتل سلم الأولويات الوطنية في أي دولة كونها تؤثر على كافة أنشطة التنمية الاقتصادية والاجتماعية، ولهذا أدركت الدول النامية ومنها الجزائر أهمية البيئة، وسعت لحمايتها ووضعها ضمن أولوياتها. فاستجابة الحكومة بإدارتها المركزية والمحلية لتجسيد نموذج المدن المستدامة في الجزائر في ظل تنامي الاختلالات في التسيير الحضري الراهن للمدن مع الوقوف على أبرز التحديات التي تحول دون ذلك لنصل الى صياغة رؤية شاملة حول فرص ومتطلبات تجسيد المدن المستدامة انطلاقا من الواقع المعاش والإمكانات المتوفرة. ومن أبرز النتائج المتوصل إليها هي عدم مواكبة نماذج المدن الجزائرية الحالية مع معايير الاستدامة الحضرية نتيجة لمجموعة من العوامل التنظيمية، الاجتماعية والثقافية...، والتي تحتاج إلى تطبيق سياسة عمرانية ترتكز على مبادئ التنمية الحضرية المستدامة ونماذج التخطيط الاستراتيجي كما تتطلب التآزر وتعاون مختلف الفواعل المحلية ونشر ثقافة الاستدامة البيئية في المحيط. الكلمات المفتاحية: السياسات البيئية، التنمية المستدامة، الإدارة المحلية، المدن المستدامة. Abstract: The research aims to know the extent of the impact of environmental policies on localities, towards more sustainable cities, and the increasing interest in the issue of protecting the environment from pollution and depletion of resources on an ongoing basis, and this environmental concern has been embodied in many forms at the local and global levels, and we find that environmental issues are among the national priorities. In any country, as it affects all economic and social development activities, and for this reason, developing countries, including Algeria, realized the importance of the environment, and sought to protect it and put it among their priorities. The government’s response, with its central and local administration, is to embody the model of sustainable cities in Algeria in light of the growing imbalances in the current urban management of cities, while standing on the most prominent challenges that prevent this in order to reach the formulation of a comprehensive vision about the opportunities and requirements for the embodiment of sustainable cities based on the lived reality and the available capabilities. Among the most prominent results reached is the failure to keep pace with the current Algerian city models with urban sustainability standards as a result of a set of organizational, social and cultural factors..., which require the implementation of an urban policy based on the principles of sustainable urban development and strategic planning models, as well as requiring the synergy and cooperation of various local actors And spreading a culture of environmental sustainability in the ocean. Keywords : environmental policies; sustainable development; Local Administration; sustainable cities
Keywords: السياسات البيئية، التنمية المستدامة، الإدارة المحلية، المدن المستدامة.